Peptidoglycan editing by a specific LD-transpeptidase controls the muramidase-dependent secretion of typhoid toxin - Geiger, Tobias (Nat Microbiol, 2018)
Protein secretion mechanisms are essential for the virulence of most bacterial pathogens. Typhoid toxin is an essential virulence factor for Salmonella Typhi, the cause of typhoid fever in humans. This toxin is unique in that it is only produced within mammalian cells, and it must be trafficked to the extracellular space prior to intoxicating target cells. An essential and poorly understood aspect of this transport pathway is the secretion of typhoid toxin from the bacterium into the S. Typhi-containing vacuole. We show here that typhoid toxin secretion requires its translocation to the trans side of the peptidoglycan layer at the bacterial poles for subsequent release through the outer membrane. This translocation process depends on a specialized muramidase, whose activity requires the localized editing of peptidoglycan by a specific LD-transpeptidase. These studies describe a protein export mechanism that is likely conserved in other bacterial species.